Peningkatan Kontrol Diri Penyalahguna Narkoba Melalui Metode Therapeutic Community dengan Static Group - Fazny, Bella Yugi; Riani, Hesty Putri; Sukmawati, Fitri (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2022)
Research Objectives: to see the effect of Therapeutic Community with Static Group on increasing self-control of drug abusers. Research Methods: This study used Counseling Guidance Action Research (PTBK), along with qualitative research methods. Participants in this study consisted of drug abusers. The sample in this study amounted to 3 residents. The data collection techniques used were questionnaires, interviews, observations, and documentation. The data analysis technique used is data reduction and data presentation. Research Results: The process of self-control of drug abusers by using Therapeutic Community with Static Groups runs smoothly so that self-control increases during the process. There is an increase in the self-control of drug abusers after being given the Therapeutic Community approach with Static Group from 6.67 percent good enough to increase after the first cycle was carried out to 28 in the high category and increased according to the researchers' expectations after the second cycle action was carried out with a percentage of 36.67 in the high category. : there is the influence of Therapeutic Community with Static Group on increasing self-control of drug abusers. Implications: residents are more focused so they can respond well when interacting. As prospective counselors who will also handle the same case to help improve the self-control of drug abusers, they must increase their knowledge and insight from now so that when meeting clients, they can better prepare themselves mentally to handle the case.